Tumor cell-secreted angiogenin induces angiogenic activity of endothelial cells by suppressing miR-542-3p. Issue 1 (1st November 2015) - He, Ting; Qi, Feifei; Jia, Lin; Wang, Shan; Wang, Chunying; Song, Nan; Fu, Yan; Li, Lin; Luo, Yongzhang
Graphic Abstract: Abstract: Therapeutic strategies for targeting angiogenesis have been proven as successful treatments for divergent cancers. We previously discovered an anti-angiogenic miR-542-3p, which directly targeted the key angiogenesis-promoting protein Angiopoietin-2 to inhibit tumor angiogenesis in breast cancer models. In this study, to further investigate the mechanism of miR-542-3p induced angiogenic inhibition, we screened for tumor cell derived factors which were responsible for miR-542-3p alteration in endothelial cells. We found that tumor cell-derived angiogenin downregulated miR-542-3p in endothelial cells. Overexpression of angiogenin in tumor cells facilitated angiogenic activation in both in vitro and in vivo models via inhibition of miR-542-3p. Furthermore, our results showed that angiogenin could suppress CEBPB and POU2F1, which were transcription factors for miR-542-3p, suggesting a novel tumor cell–endothelial cell signal pathway. In addition, the level of angiogenin in primary breast carcinomas correlated with clinical progression. Serum levels of angiogenin were associated with metastatic development of breast cancer patients. Together, these findings reveal a novel regulatory pathway whereby tumor-derived angiogenin directly activates angiogenesis through inhibition of miR-542-3p, suggesting that angiogenin may represent a promising target for anti-angiogenic therapy and a potential marker for monitoring disease progression.